<span><span><span><span>4x</span>−<span>2y</span></span>+z</span>=8 </span>Step 1: Add 2y to both sides <span><span><span><span><span>4x</span>−<span>2y</span></span>+z</span>+<span>2y</span></span>=<span>8+<span>2y</span></span></span><span><span><span>4x</span>+z</span>=<span><span>2y</span>+8 </span></span>Step 2: Add -z to both sides <span><span><span><span>4x</span>+z</span>+<span>−z</span></span>=<span><span><span>2y</span>+8</span>+<span>−z</span></span></span><span><span>4x</span>=<span><span><span>2y</span>−z</span>+8 </span></span>Step 3: Divide both sides by 4 <span><span><span>4x</span>4</span>=<span><span><span><span>2y</span>−z</span>+8</span>4</span></span><span>x =<span><span><span><span>1/2</span>y</span>+<span><span><span>−1/</span>4</span>z</span></span>+<span>2
</span></span></span><span><span><span>−y</span>+z</span>=4 </span>Step 1: Add -z to both sides <span><span><span><span>−y</span>+z</span>+<span>−z</span></span>=<span>4+<span>−z</span></span></span><span><span>−y</span>=<span><span>−z</span>+4 </span></span>Step 2: Divide both sides by -1 <span><span><span>−y</span><span>−1</span></span>=<span><span><span>−z</span>+4</span><span>−1</span></span></span><span>y
=<span>z−<span>4
</span></span></span><span><span>2z</span>=4 </span>Step 1: Divide both sides by 2 <span><span><span>2z/</span>2</span>=<span>4/2 </span></span><span>=z=2</span><span> </span> <span>